The Effect of Heavy Water Waste on the Euphrates River in Increasing the Concentration of Some Heavy Metals: Pengaruh Limbah Air Berat di Sungai Eufrat dalam Meningkatkan Konsentrasi Beberapa Logam Berat - Jawed, Sanaa T.; Shihab , Ahmed Fareed (Procedia of Engineering and Life Science, 2024)
General Background: The Euphrates River, a vital water source for the Thi Qar Province, is increasingly threatened by pollution, particularly from heavy water waste. Specific Background: The river’s proximity to industrial activities, notably a thermal power station, has led to elevated concentrations of heavy metals, raising concerns about environmental and public health. Knowledge Gap: While prior studies have focused on water quality in various regions, there is limited research on the specific impact of heavy water waste on the Euphrates River’s heavy metal concentrations. Aims: This study aims to assess the concentration of heavy metals in the Euphrates River’s water and sediment, investigate the sources of pollution, and evaluate the effectiveness of current waste management practices. Results: The study, conducted from summer 2022 to spring 2023, revealed that in water samples, heavy metal concentrations followed the order Zn>Cu>Cr>Ni>Pb>Cd, while in sediment, the order was Ni>Zn>Cu>Pb>Cr>Cd. Station 1, near the Nasiriyah thermal power station, exhibited the highest metal concentrations, emphasizing the influence of industrial pollution. Novelty: This research provides the first comprehensive assessment of heavy metal contamination in the Euphrates River linked specifically to heavy water waste, highlighting the critical impact of industrial discharges. Implications: The findings underscore the urgent need for enhanced regulation and maintenance of heavy water treatment plants, as well as public awareness campaigns to mitigate pollution. Implementing these measures is crucial for protecting the river’s ecosystem and the health of communities relying on its waters Highlights: Station 1: Highest heavy metal levels near the thermal power station. Industrial Waste: Major source of river pollution in the study area. Call to Action: Strengthen regulations and raise public awareness on water protection. Keywords : Heavy Metals, Euphrates River, Water Pollution, Sediment Contamination, Industrial Waste